Free Will, Causality, and Neuroscience - Feltz, Bernard; Missal, Marcus; Sims, Andrew (Cognitive Science, 2019)
This book aims to show that recent developments in neuroscience permit a defense of free will. Through language, human beings can escape strict biological determinism. Readership: All interested in the philosophy of sciences, in the philosophy of mind, in the philosophy of language, in the cognitive sciences, in anthropology, and anyone interested by the question of the relation between brain and free will.